Impact of Curcuma mangga Val. Rhizome Essential Oil to p53, Bcl-2, H-Ras and Caspase-9 expression of Myeloma Cell Line - Endang Astuti; Retno Sunarminingsih; Umar Anggara Jenie; Sofia Mubarika; S. Sismindari (Universitas Gadjah Mada, 2014)
Cancer is a disease, a public health problem, which is found in the world as well as in Indonesia. Ingeneral, some of cancer theraphies are ineffective, characterized by the resistance performance of cancer cell line,the exposed normal cell and by the side effects. Nowadays, studies to fi nd the specifi c and safely anti-cancerdrugs were increased by the time. Several studies revealed that Curcuma mangga Val. Rhizome contains somesecondary metabolites, essential or non-essential oil, which has cytotoxic activities to the cancer cells. Basedon these anti-cancer potentials, this study has several aims to recognize anti-cancer selectivity and molecularmechanism by inducting apoptosis and inhibiting myeloma cell proliferation. To C. mangga Val. essential oil,immunocyto chemical test was performed to determine the expression of p53, caspase-9, Bcl-2, H-Ras proteinwhile TUNEL test was performed to determine the number of apoptosis cells.The results of this study shown that anti-cancer molecular mechanism of C. mangga Val. essential oil tomyeloma cell line was performed by increasing apoptosis; by increasing the expression of pro-apoptosis p53,caspase-9 protein and reducing protein which is increasing proliferation Bcl-2 and H-Ras.